2005
DOI: 10.1016/j.cell.2005.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Rab Conversion as a Mechanism of Progression from Early to Late Endosomes

Abstract: The mechanisms of endosome biogenesis and maintenance are largely unknown. The small GTPases Rab 5 and Rab 7 are key determinants of early and late endosomes, organizing effector proteins into specific membrane subdomains. Whether such Rab machineries are indefinitely maintained on membranes or can disassemble in the course of cargo transport is an open question. Here, we combined novel image-analysis algorithms with fast live-cell imaging. We found that the level of Rab 5 dynamically fluctuates on individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

81
1,549
4
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,476 publications
(1,644 citation statements)
references
References 47 publications
(50 reference statements)
81
1,549
4
10
Order By: Relevance
“…Loss of the HOPS complex would then render RAB-7(+) phagosomes unable to mature into later lysosomal structures. Other studies have shown that the recruitment of Rab7 to endosomes is linked to Rab5 activity; hence, HOPS complex members can also be found in a complex 39 with Rab5 GTPÃS . We find that knockdown of one complex member, vps-41 resulted in an increase in the number of corpses in RAB-5(+) phagosomes, suggesting that in the nematode, VPS-41 may be involved in the recruitment of the HOPS complex to maturing RAB-5(+) phagosomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of the HOPS complex would then render RAB-7(+) phagosomes unable to mature into later lysosomal structures. Other studies have shown that the recruitment of Rab7 to endosomes is linked to Rab5 activity; hence, HOPS complex members can also be found in a complex 39 with Rab5 GTPÃS . We find that knockdown of one complex member, vps-41 resulted in an increase in the number of corpses in RAB-5(+) phagosomes, suggesting that in the nematode, VPS-41 may be involved in the recruitment of the HOPS complex to maturing RAB-5(+) phagosomes.…”
Section: Discussionmentioning
confidence: 99%
“…If this were the case, we would predict that RAB-5 and RAB-7 would co-localize only transiently on phagosomes, during ÃRab conversionà 39 . When we made double transgenic worms expressing both YFP::RAB-5 and CFP::RAB-7, we found minimal co-localization between these two markers ( Figure 1, iÃl, arrows vs. arrowheads).…”
Section: Rab-5 and Rab-7 Are Required For Efficient Phagosome Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Influenza viruses are preferentially delivered, by microtubule-dependent transport, to the dynamic early endosomes 27 . Viral fusion typically occurs in the midst of the endosomal maturation process with both early and late endosomal markers present on the endosomean intermediate state of endosomal maturation that has only recently been discovered [27][28][29] .…”
Section: Viral Entrymentioning
confidence: 99%
“…The upstream part of the pathway is characterized by endosomal maturation, whereby Rab5-containing early endosomal vesicles gradually mature into Rab7-containing late endosomes (LEs) through Rab conversion [8], mediated by the Rab7 guanine nucleotide exchange factor (GEF) complex Mon1-Ccz1 [9,10]. In contrast, the downstream delivery of material from LEs to lysosomes is thought to occur by transient and permanent fusion between LEs and lysosomes [11].…”
Section: Introductionmentioning
confidence: 99%